Development of an Inquiry-Transactional Based Learning Model for Historical Aspects of Moral Education in Junior High Schools - Liu Tan; Hemming Shan (International Journal of Educational Technology and Artificial Intelligence, 2023)
The purpose of this research is to develop a model of learning material for the history of the development of culture in the world and China. The study uses research and development methods. Learning materials are developed based on an inquiry approach - transactional. The research was conducted at a junior high school, involving 8 experts, 26 students and 2 teachers, 2 education officers, and parents. The results of the study are: (1) a conceptual model of learning design for historical material on the development of culture in the world; (2) learning design procedural models to develop learning materials; (3) a set of models of learning materials for the history of cultural development in the world, consisting of printed materials, interactive multimedia, teacher guides, and teaching aids.